Combination of neurofilament heavy chain and complement c3 as CSF biomarkers for ALS - Ganesalingam, Jeban (2011)
Amyotrophic lateral sclerosis (ALS) is a rapidly progressive and ultimately fatal neurodegenerative disease with an average survival of 3 years from symptom onset. Rapid and conclusive early diagnosis is essential if interventions with disease-modifying therapies are to be successful. Cytoskeletal modification and inflammation are known to occur during the pathogenesis of ALS. We measured levels of cytoskeletal proteins and inflammatory markers in the cerebrospinal fluid (CSF) of ALS, disease controls and healthy subjects. We determined threshold values for each protein that provided the optimal sensitivity and specificity for ALS within a training set, as determined by receiver operating characteristic (ROC) analysis. Interestingly, the optimal assay was a ratio of the levels for phosphorylated neurofilament heavy chain and complement C3 (pNFH/C3). We next applied this assay to a separate test set of CSF samples to verify our results. Overall, the predictive pNFH/C3 ratio identified ALS with 87.3% sensitivity and 94.6% specificity in a total of 71 ALS subjects, 52 disease control subjects and 40 healthy subjects. In addition, the level of CSF pNFH correlated with survival of ALS patients. We also detected increased pNFH in the plasma of ALS patients and observed a correlation between CSF and plasma pNFH levels within the same subjects. These findings support large-scale prospective biomarker studies to determine the clinical utility of diagnostic and prognostic signatures in ALS.